1996
DOI: 10.2166/wst.1996.0203
|View full text |Cite
|
Sign up to set email alerts
|

Influence of bacterial extracellular polymers on the membrane separation activated sludge process

Abstract: The objective of this study is to elucidate influence of bacterial extracellular polymers (EPS) on the performance of the submerged membrane separation activated sludge process (SMAS). Hollow fiber membrane modules were submerged in laboratory-scale reactors and the permeate was pulled out from the modules by suction pumps. Acetic acid was used as a carbon source and peptone or ammonium nitrogen was used as a nitrogen source in the substrate. The change of EPS amount both in the mixed liquor and on the membran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
111
4

Year Published

1998
1998
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(118 citation statements)
references
References 0 publications
3
111
4
Order By: Relevance
“…This observation apparently differs from analysis reported by [21] where the method of extraction and mode of measurement (as TOC or as Carbohydrates and Proteins) are different. Also [22] commented that high EPS causes high viscosity and accumulation on the membrane surface leading to increase in the filtration resistance. On account of such diversified inferences supported from various methods of analysis and different definitions of EPS fractions, the comparison of outcomes is rather difficult as also stated by [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This observation apparently differs from analysis reported by [21] where the method of extraction and mode of measurement (as TOC or as Carbohydrates and Proteins) are different. Also [22] commented that high EPS causes high viscosity and accumulation on the membrane surface leading to increase in the filtration resistance. On account of such diversified inferences supported from various methods of analysis and different definitions of EPS fractions, the comparison of outcomes is rather difficult as also stated by [23].…”
Section: Discussionmentioning
confidence: 99%
“…The MLSS is not well correlated with any of the parameters mentioned in Table 2; a weak positive correlation with DSVI and free EPS (as TOC) can be attributed to extracellular organic materials influencing the settling behaviour at higher MLSS. Few researches [22,26] commented that filtration resistance increases with increase in MLSS; and more recent researches [21,27,28] suggest that MLSS can possibly correlate with fouling/filtration related parameters only at very high concentrations. Visual inspection confirmed the crucial role of sludge conditioning (see Fig.…”
Section: ) Mlss and (Mlvss/mlss) Ratio (C) Capillary Suction Time (mentioning
confidence: 99%
“…Li et al (2007b) investigated aerobic granulation in membrane bioreactor, and measured the total extracellular polymeric substances (EPS) contents on day 5 as 39.6 mg gSS − 1 , and as 749.5 mg gSS − 1 on day 28. Nagaoka et al (1996) had suggested that EPS adsorbed on the surface of aerobic biogranules led to increased water content and loose-structure of biogranules.…”
Section: Sbr Operationmentioning
confidence: 99%
“…Suspended solids are very often identified as a main foulant (Defrance et al, 2000;Bae et al, 2005) where the significance of the submicron colloidal fraction in the SS has been reported to correlate with membrane fouling rates (Wisniewski et al, 2000;Li et al, 2005;Rosenberger et al, 2006). In MBR processes fouling has also been attributed to extracellular polymeric substances (EPS) and soluble microbial products (SMP) (Nagaoka et al, 1996;Chang et al, 2002;Li et al, 2005;Rosenberger et al, 2006).…”
Section: Introductionmentioning
confidence: 99%